Environmental Biology - Fisher, Matthew R.; Open Textbook Library (Open Textbook Library, 2018)
This open textbook covers the most salient environmental issues, from a biological perspective. The text is designed for an introductory-level college science course. Topics include the fundamentals of ecology, biodiversity, pollution, climate change, food production, and human population growth.
Chapter 1: Environmental Science -- Chapter 2: Matter, Energy, & Life -- Chapter 3: Ecosystems and the Biosphere -- Chapter 4: Community & Population Ecology -- Chapter 5: Conservation & Biodiversity -- Chapter 6: Environmental Hazards & Human Health -- Chapter 7: Water Availability and Use -- Chapter 8: Food & Hunger -- Chapter 9: Conventional & Sustainable Agriculture -- Chapter 10: Air Pollution, Climate Change, & Ozone Depletion -- Chapter 11: Conventional & Sustainable Energy
In English.
Description based on print resource
Keywords: Biology -- Textbooks